Software-based video analysis of functional outcomes of face transplantation - Fischer, Sebastian; Diehm, Yannick; Kotsougiani-Fischer, Dimitra (Microsurgery, 2019)
Introduction Assessment of outcomes after face transplantation (FT) is necessary to provide sound evidence on the benefits of this life-giving surgery. Current methods for outcomes assessment, however, are imprecise or prone to subjectivity. Software-based video analysis may allow fast, objective and retrospective assessment of restoration of facial movements and functions after FT. Patients and methods We recorded videos of 7 subjects before as well as every 3-6 months after facial transplantation. Patients performed the same sequence of facial movements in every video: smile, open mouth, purse lips, wrinkle nose, frown, close eyes, and lift eyebrows. The videos were retrospectively analyzed using EMOTIENT software, which is capable of automatic tracking and detailed measurements of facial movements and expressions. These measurements were subsequently compared to the same patient at different time points, as well as to the normal population. Results Open mouth, wrinkle nose and smile functions significantly improved in all patients when compared to pre-transplant functions; this improvement was significant at 3, 6, and 12 months after transplant, respectively. Lip purse, eye closure and frown functions improved by 6, 9, and 18 months after transplantation, respectively; however, improvement in these particular functions was not significantly with respect to pre-transplant. Face transplantation did not improve any of the patients' ability to lift their eyebrows. Most remarkably, mouth opening and smiling functions both reached values comparable to the normal population at 3 and 12 months after transplantation, respectively. Conclusion Software-based video analysis provides a valuable assessment tool capable of objective, precise and reproducible analysis of facial movements and functions after FT.
First published: 29 August 2018
Gesehen am 05.07.2019